A Comparative Study of Sound Localization Algorithms for Energy Aware Sensor Network Nodes - Julian, Pedro Marcelo (2004)
Sound localization using energy-aware hardware for sensor networks nodes is a problem with many applications in surveillance and security. In this paper, we evaluate four algorithms for sound localization using signals recorded in a natural environment with an array of commercial off-the-shelf microelectromechanical systems microphones and a specially designed compact acoustic enclosure. We evaluate performance of the algorithms and their hardware complexity which relates directly to energy consumption.